An Insight Into Pathophysiology, Epidemiology, and Management of Cardiovascular Complications of SARS-CoV-2 Infection, Post-acute COVID Syndrome, and COVID Vaccine. Issue 3 (28th April 2022) - Davoudi, Farideh; Miyashita, Satoshi; Yoo, Tae Kyung; Lee, Patrick T.; Foster, Gabriel P.
Abstract : Coronavirus disease 2019 (COVID-19), the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was declared a pandemic health emergency in March 2020. Elderly patients and those with pre-existing medical conditions including cardiovascular disease are at increased risk of developing severe disease. Not only is the viral infection with SARS-CoV-2 associated with higher mortality in patients with underlying cardiovascular disease, but development of cardiovascular complications is also common in patients with COVID-19. Even after recovery from the acute illness, post-acute COVID syndrome with cardiopulmonary manifestations can occur in some patients. Additionally, there are rare but increasingly recognized adverse events, including cardiovascular side effects, reported with currently available COVID-19 vaccines. In this review, we discuss the most common cardiovascular complications of SARS-CoV-2 and COVID-19 vaccines, cardiopulmonary manifestations of post-acute COVID syndrome and the current evidence-based guidance on the management of such complications.